Prevalence and clinicopathological Spectrum of Auto-Immune Liver Diseases & Overlap syndrome - Annapoorani Varadarajan; Archana Rastogi; Rakhi Maiwall; Chhagan Bihari; Sherin Thomas; Vikrant Sood; Saggere Muralikrishna Shasthry (Indian Journal of Pathology and Microbiology)
Aims: Autoimmune liver diseases (AILD) represent a spectrum of related yet distinct immune-mediated disorders. The literature on the prevalence of these AILDs in Indian population is scarce. This study aims to assess the prevalence and clinicopathological spectrum of various AILDs especially the overlap syndrome. Materials and Methods: A 10-year (2011–2020) cross-sectional, retrospective observational study of histological proven cases of AILD was conducted. Clinical, demographic, and laboratory parameters were retrieved. Two pathologists independently reviewed the liver biopsies and reassessed 18 histopathological parameters. Results: During the study period, 17664 liver biopsies were received, out of which 1060 (6%) biopsies of AILD were identified. After exclusion, we had 721 cases which revealed a distribution of autoimmune hepatitis (AIH)-64.7%, primary biliary cholangitis (PBC)-14.8%, primary sclerosing cholangitis (PSC)-7.6%, overlap AIH-PBC 11%, and overlap AIH-PSC 1.7%. AIH patients had significantly higher prevalence for severe lobular inflammation (27%, P ≤ 0.001), several lobular plasma cells (37%, P ≤ 0.001), central perivenulitis (30%, P ≤ 0.001), hepatic rosettes (51%, P ≤ 0.001), and necrosis (35.5%, P ≤ 0.001), while PBC patients had significantly higher frequency of florid duct lesions (11.2%, P ≤ 0.001), duct loss (83.17%, P ≤ 0.001), bile duct damage (76.6%, P ≤ 0.001), and periportal copper deposits (19.6%, P ≤ 0.001). Overlap AIH-PBC group had the highest proportion of severe portal inflammation (27.5%, P ≤ 0.001), prominent portal plasma cells (75%, P ≤ 0.001), moderate interface activity (53.7%, P ≤ 0.001), Mallory-Denk bodies (27.5%, P ≤ 0.001), and periportal cholate stasis (25%, P ≤ 0.001). Conclusion: Prevalence of biopsy-proven AILDs in our study cohort is 6%. AIH (64.7%) is the most common AILD followed by PBC (14.8%). Overlap syndrome (AIH-PBC) showed prevalence of 11%.